Significance of Nodal Metastasis in Parotid Gland Acinar Cell Carcinoma. (8th August 2020) - Moon, Peter; Tusty, Mahbuba; Divi, Vasu; Megwalu, Uchechukwu C.
Abstract : Objectives: To evaluate the rate of lymph node metastasis in parotid gland acinar cell carcinoma, to identified factors associated with increased risk of metastasis, and to evaluate the effect of nodal metastasis on survival. Methods: This is a retrospective cohort study utilizing data from a large population‐based cancer database. Data were extracted from the Surveillance, Epidemiology, and End Results (SEER) 18 database. The study cohort included patients with parotid gland acinar cell carcinoma diagnosed between 2000 and 2015. Results: The overall rate of lymph node metastasis was 6.8%. T3/T4 (OR 6.17, 95% CI, 3.03 to 13.16) disease along with High Grade (OR 15.95) disease were associated with increased risk of nodal metastasis. Non‐white, non‐Black race was associated with decreased risk. Age and sex were not associated with nodal metastasis. Nodal metastasis was associated with worse OS (HR 6.27, 95% CI, 3.85 to 10.20) and DSS (HR 6.96, 95% CI, 3.81 to 12.73) after adjusting for covariates. Conclusion: Parotid gland acinar cell carcinoma carries a low risk of nodal metastasis. Both advanced T stage and high grade are associated with increased risk of nodal metastasis. Nodal metastasis is associated with decreased overall survival. Level of Evidence: 3 Laryngoscope, 131:E1125–E1129, 2021